A smart ROS/NIR dual-responsive melanin delivery platform for photoacoustic imaging-guided osteoarthritis therapy. (December 2021) - Ruan, Jihao; Yu, Qili; Cui, Haomin; Qin, Xing; Qin, Limei; Chen, Shuai; Niu, Dechao; Fan, Cunyi
Highlights: DHMP/M displays splendid biological functions for OA therapy by scavenging free radicals via TLR-2/MAPK/Akt signaling. DHMP/M possess a unique long-term controlled-release behavior and short-burst release capability. DHMP/M has a good photoacoustic imaging ability, guaranteeing the bio-safety of OA therapy. ABSTRACT: Oxidative stress is considered an efficient therapeutic target in the progression of osteoarthritis (OA). Unfortunately, the current drug delivery system for the reactive oxidative species (ROS) scavengers is still unsatisfactory due to their insufficient responsiveness and rapid joint clearance. In this study, we design and develop a smart anti-oxidative agent by constructing a dual-responsive hybrid micelle with free radical scavenger melanin in the micellar core and polydopamine on the shell (designated as DHMP/M) for photoacoustic imaging-guided knee OA therapy. The resulting DHMP/M displays a unique long-term controlled-release behavior involving the slow and persistent release under endogenous ROS stimuli and short-burst release capability triggered by exogenous near-infrared (NIR) light. More importantly, DHMP/M possesses excellent free radical scavenging capacity and protective effects in chondrocytes in vitro and in in vivo rat OA models. Additionally, DHMP/M exhibits efficacious photoacoustic (PA) imaging for adjusting the therapy on demand. The RNA-Seq assay of rats further shows a significant reduction of TLR-2 in the OA cartilage, revealing that DHMP/M can protected OA from inflammation via TLR-2/MAPK/Akt signaling. Consequently, the present ROS/NIR dual-responsive melanin delivery platform together with PA imaging-monitoring provides a precise theranostic strategy for OA therapy. Graphical Abstract: Graphical Abstract Image, graphical abstract .